Incongruent visual cues affect the perception of Mandarin vowel but not tone - Shanhu Hong; Shanhu Hong; Rui Wang; Biao Zeng; Biao Zeng (Frontiers in Psychology, 2023)
Over the recent few decades, a large number of audiovisual speech studies have been focusing on the visual cues of consonants and vowels but neglecting those relating to lexical tones. In this study, we investigate whether incongruent audiovisual information interfered with the perception of lexical tones. We found that, for both Chinese and English speakers, incongruence between auditory and visemic mouth shape (i.e., visual form information) significantly interfered with reaction time and reduced the identification accuracy of vowels. However, incongruent lip movements (i.e., visual timing information) did not interfere with the perception of auditory lexical tone. We conclude that, in contrast to vowel perception, auditory tone perception seems relatively impervious to visual congruence cues, at least under these restricted laboratory conditions. The salience of visual form and timing information is discussed based on this finding.